The Scottish Idealists : Selected Philosophical Writings. - Boucher, David (Library of Scottish philosophy., 2012)
The extent to which British Idealism was heavily influenced by Scots has been little noticed, yet not only were they at the forefront of introducing Hegel into Britain in the work of Ferrier, Carlyle, Hutcheson, Stirling and Edward Caird, but they were also distinctive in locating themselves in relation to the Scottish philosophical tradition they sought to extend. The Scottish Idealists, among them Edward Caird, David George Ritchie, Andrew Seth Pringle Pattison, William Mitchell, John Wats ...